The Value of an Ecosystem-Based Approach to Organizational Sustainability: The Case of a Hybrid Sports-Based Youth Development Social Venture in the US South - Monhartova, Anna; Murphy, Laura (Journal of Strategic Innovation and Sustainability, 2021)
This article explores complexity-thinking, non-linear-based models for non-profit entities aiming to create a systemic change. It applies an ‘enriched’, ecosystems approach that accounts for non-linear inputs-outputs, tipping points, dynamic contexts, and human, non-human, and institutional actors, capturing the various relationships and their multi-directional characteristics. It introduces additional factors, such as feedback loops and emergent changes, that can allow an organization to find new strategies towards sustainability and social impact. We apply this ecosystem model to social entrepreneurial organizations operating in the field of sports-based youth development via the case of A’s & Aces, drawing from first-hand experience and organizational data.